Some Aspects of Leadership in Independent Schools in Alberta - Decoux, Bruce V.; Holdaway, Edward A. (Alberta Journal of Educational Research, 1999)
Interest in independent schools has been growing in Canada, partly as a result of some parental dissatisfaction with public schools. The Canadian province of Alberta has legislation in place that permits development of independent schools while simultaneously imposing controls on their operations. A recent study used interviews, observations, and documents to examine the perceptions of principals in eight accredited, funded, independent schools in Alberta about the major factors that affected their leadership role. They especially identified philosophical congruence enhanced by respect and trust, as well as personal relationships, school culture, symbolism, and support from staff of the government's regional offices.